Relación entre la inversión pública en funciones básicas para el desarrollo y la pobreza en el departamento de Loreto 2007 – 2021 - García García, German Gustavo (2023)
The levels of monetary poverty in Loreto are above the average in the country, although it is true that it has been reduced from 57.5% in 2007 to 32.2% in 2019 and a slight increase to 33.1% in 2020 (INEI, 2022). This indicates that around 1/3 of the population is still living in poverty, which is worrying. In this context, the objective of the research is to determine the relationship that exists between public investment to encourage the economic and social development of the department of Loreto, it will serve as a basis for policy makers to make better decisions in order to reduce poverty; For this we use a quantitative methodology of a non-experimental nature and a correlational design and we find that there is a linear and monotonous negative relationship between public investment and the level of poverty in the department of Loreto during the period 2007-2021, and this relationship is negative and relatively high (greater than 50%) showing a coefficient value of -0.6920642, or in other words a correlation coefficient of 69.2%.